Multifunctional Smart Skin Adhesive Patches for Advanced Health Care - Hwang, Insol; Kim, Hong Nam; Seong, Minho; Lee, Sang-Hyeon; Kang, Minsu; Yi, Hoon; Bae, Won Gyu; Kwak, Moon Kyu; Jeong, Hoon Eui (WILEY, 2018)
A skin adhesive patch is the most fundamental and widely used medical device for diverse health-care purposes. Conventional skin adhesive patches have been mainly utilized for routine medical purposes such as wound management, fixation of medical devices, and simple drug release. In contrast to traditional skin adhesive patches, recently developed patches incorporate multiple key functions of bulky medical devices into a thin, flexible patch based on emerging nanomaterials and flexible electronic technologies. Consequently, the meaning of the term skin adhesive patch becomes broader and smarter compared to the traditional term. This review summarizes recent efforts undertaken in the development of multifunctional advanced skin adhesive patches, and briefly describes future directions and challenges toward the next generation of smart skin adhesive patches for ubiquitous personalized health care.
Keywords: TRANSDERMAL DRUG-DELIVERY; PRESSURE-SENSITIVE ADHESIVES; BIOINSPIRED DRY ADHESIVES; EPIDERMAL ELECTRONICS; SCALABLE FABRICATION; MEDICAL ADHESIVES; PROTEIN DELIVERY; SUCTION CUPS; GECKO SETAE; MICRONEEDLES